2021
DOI: 10.1186/s12913-021-06947-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pediatric hospital care during the COVID-19 pandemic: a national qualitative study

Abstract: Background The COVID-19 pandemic has necessitated rapid changes in healthcare delivery in the United States, including changes in the care of hospitalized children. The objectives of this study were to identify major changes in healthcare delivery for hospitalized children during the COVID-19 pandemic, identify lessons learned from these changes, and compare and contrast the experiences of children’s and community hospitals. Methods We purposefully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Despite the toll of this constant state of alert on individuals, teams, and organizations, the abrupt change in working practices and priorities also brought invaluable learnings as leaders, teams, and individual staff responded to the crisis (Penwill et al. , 2021; Salvador-Carulla et al.…”
Section: Organizational Learning and Organizational Change In Healthc...mentioning
confidence: 99%
“…Despite the toll of this constant state of alert on individuals, teams, and organizations, the abrupt change in working practices and priorities also brought invaluable learnings as leaders, teams, and individual staff responded to the crisis (Penwill et al. , 2021; Salvador-Carulla et al.…”
Section: Organizational Learning and Organizational Change In Healthc...mentioning
confidence: 99%
“…Furthermore, it may reflect the hesitancy to seek care in the early phase of the pandemic, which may be due to any social stigma, fear, or false belief due to misinformation by the parents. (15)(16)(17)(18) Further study should be carried out to properly understand the differences, as this can help in future pandemics. Moreover, differences between the variants in April and late 2020 and their impact on children should also be compared.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Penwill et al, describe how the pandemic has changed pediatric hospitals in terms of communication, staffing models, and addressing mental health in an evolving environment. They found that caregivers reported “hardships with decreased access to certain supports such as child life services and visitor restrictions” 11 . Penwill et al 11 further described that communication rapidly declined as staff did not enter rooms as frequently, patients were discharged early especially if they were immunocompromised to minimize COVID exposure, and translation services were no longer present in house.…”
Section: Introductionmentioning
confidence: 99%
“…They found that caregivers reported “hardships with decreased access to certain supports such as child life services and visitor restrictions” 11 . Penwill et al 11 further described that communication rapidly declined as staff did not enter rooms as frequently, patients were discharged early especially if they were immunocompromised to minimize COVID exposure, and translation services were no longer present in house. There is a necessity to remember the strategies used in the past and improvise our practice as conditions change.…”
Section: Introductionmentioning
confidence: 99%